Active viscous damping system with amplifying braces for control of MDOF structures. - Gluck, J. (Earthquake engineering & structural dynamics.)
The development and the applications of an active controlled viscous damping device with amplifying braces are described. The system of the dampers, defined as active viscous damping system (AVDS), connected to an amplifying brace (AB) is presented herein. Instantaneous control theory with velocity and acceleration feedback is used to obtain the control forces at each time step during an excitation. Control of the damping forces is possible due to the mechanical structure of the proposed AVDS, and the connection to the AB. The proposed system can be efficiently used to enhance the damping of a structure without modifying its stiffness. The added damping forces can be adjusted in a wide range. The efficiency of the presented system is demonstrated by a numerical simulation of a seven storey building subjected to earthquakes. The simulation shows a considerable reduction of control forces required for control to the AVDS with AB, compared to the same system without AB.